FINANCIAL MANAGEMENT BEHAVIOR PELAKU UMKM DAERAH WISATA PESISIR MADURA: INCOME, FINANCIAL LITERACY, & FINANCIAL SELF-EFFICACY - NURUL FADILA; PURNAMAWATI (Universitas Islam Balitar, 2023)
MEA has determined that it provides a great opportunity for the MSME sector to develop, but on the other hand it is also a threat to MSMEs. The obstacle that generally occurs in managing MSMEs for MSME actors is not understanding how to manage business finances properly. This is the main obstacle for MSMEs to be able to develop their business. There are factors that can influence financial management behavior variables such as income, financial literacy, financial self-efficacy and others. This research was conducted with the aim of knowing whether there is an influence between income, financial literacy, and financial self-efficacy on financial management behavior. The data were obtained from the results of interviews and filling out questionnaires to MSMEs in the Madura coastal tourism area, especially Pamekasan and Sumenep Regencies with a total of 60 respondents. The findings from this research are income, financial literacy, and financial self-efficacy have an influence on financial management behavior.